On the nomenclature of fossil Stuckenia (Potamogetonaceae) - Doweld, Alexander Borisovitch (Phytotaxa, 2015)
15 fossil species of Potamogeton subgen. Coleogeton, described from the Oligocene to Pleistocene sediments of Eurasia, based on fruit endocarp and leaf imprints findings, were recombined into a newly reinstated distinct genus Stuckenia Börner: S. aldanensis (Dorof.) Doweld, comb. nov., S. arctovaginata (Dorof.) Doweld, comb. nov., S. carbonata (Dorof.) Doweld, comb. nov., S. clavata (Dorof.) Doweld, comb. nov., S. gibbosa (Dorof. & Wieliczk.) Doweld, comb. nov., S. matyrensis (Dorof.) Doweld, comb. nov., S. omoloica (Dorof.) Doweld, comb. nov., S. palaeofiliformis (Dorof.) Doweld, comb. nov., S. praepectinata (Negru) Doweld, comb. nov., S. praevaginata (Dorof.) Doweld, comb. nov., S. pseudorostrata (Dorof.) Doweld, comb. nov., S. sakmarensis (Dorof.) Doweld, comb. nov., S. tenuicarpa (C. Reid & E. Reid) Doweld, comb. nov., S. vaginatoides (Dorof.) Doweld, comb. nov., S. mirabilis (Kutuzk.) Doweld, comb. nov. Nomenclature and typification of species names are given along with their palaeogeographic and stratigraphic data. In addition, a neotype has been designated for S. tenuicarpa (C. Reid & E. Reid) Doweld, comb. nov.